“I’m the best! Or am I?”: Academic self-concepts and self-regulation in kindergarten - Compagnoni, Miriam; Losenno, Kelsey Marie (Frontline Learning Research, 2020)
In this paper, we examined how kindergarteners’ self-evaluation biases are related to behavioural self-regulation (SR) and learning goal orientation (GO). According to educational research and practice, fostering high and optimistic academic self-concepts promotes the setting of challenging goals and initiates effective behavioural SR processes. However, research on metacognition states that it is a match between academic self-concept and abilities that provides the optimal conditions for behavioural SR and a learning GO. There is theoretical and empirical evidence in favour of both positions, yet the correlates of self-evaluative tendencies may differ with children’s different levels of achievement, which are rarely considered. This cross-sectional study used response surface analysis, an innovative research methodology capable of assessing the complex interaction of academic self-concept and academic abilities on the behavioural SR and GO of 147 kindergarten children (M = 6.47 years, SD = 0.39 years). Polynomial regression models were used to test the presence of a fit pattern in empirical data and offer a new perspective on the interaction of academic self-concept and academic abilities. Results showed that a fit is generally associated with better behavioural SR and a learning GO but that correlates of academic self-concept differ with different achievement levels and outcome measures. This study extends current knowledge, as it offers important insights on how to conceptualise and pursue questions regarding self-concepts and behavioural SR. At an applied level, the findings indicate that interventions with kindergarteners that target SR should take the interactions between self-evaluation biases and ability level into account.